Perancangan Arsitektur Sistem Informasi Berbasis Website Menggunakan Kerangka Kerja Zachman - Pini Singgrit; Fathin Putri A; M Iqbal Alparizi; Novandra Hanifah N (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2022)
SPP payments still often experience problems such as data collection and payment information processing which is done manually where record reports still use the ledger, making work neglected and spending a lot of time and financial energy in searching student data and archiving. In the current technological era, there is a need for innovation in the use of technology in the world of education to help school financial administration so that data collection and payment information processes run effectively and efficiently. In this journal, we will discuss the design of a web-based SPP payment information system. This design aims to assist the finance department in recording tuition payments and as a means of informing payments to parents of students/guardians. The research method used is the Zachman Framework method. This website helps the finance department in recording SPP payments and parents / guardians get payment information every month.